The Black Press in Brazil: framing analyses of the content produced by the websites Correio Nagô, Mundo Negro, and Nação Z (Intercom - Brazilian Journal of Communication Sciences, 2024)
This paper aims to analyze the Black Press in Brazil and its role in the production of journalistic narratives from the perspective of Blackness, understanding the contemporary Black Press based on the fact of the content it produces, as well as based on content analysis and framing analysis. To this end, bibliographical and documentary research was carried out on Blackness and the Black Press, as well as an analysis of the content produced by the websites Correio Nagô, Mundo Negro and Nação Z, selected for their importance, to investigate three framings: how they are presented, their approaches and what they emphasize. It was possible to observe that the Black Press in Brazil makes contents that underline framing analyses in which the Black person is the main character of the journalistic narratives, contributing with inclusion from the point of view of Blackness to the open debate on several issues.
Keywords: Black Press. Blackness. Popular Communication. Framing. Journalism.